Late Antique Sigillata Tablewares in Albania - Shkodra-Rrugia, Brikena (Rei Cretariae Romanae Fautorum Acta, 2017)
This paper aims to give a comprehensive account of the imported fine table wares in the territory of modern Albania in terms of their typology and distribution. It will focus on the available typological evidence of African Red Slip, Phocean Red Slip and Cypriot Red Slip, the main recorded fine wares in Late Roman Albania.